The ALMaQUEST survey – III. Scatter in the resolved star-forming main sequence is primarily due to variations in star formation efficiency. (24th January 2020) - Ellison, Sara L; Thorp, Mallory D; Lin, Lihwai; Pan, Hsi-An; Bluck, Asa F L; Scudder, Jillian M; Teimoorinia, Hossen; Sánchez, Sebastian F; Sargent, Mark
ABSTRACT: Using a sample of 11 478 spaxels in 34 galaxies with molecular gas, star formation, and stellar maps taken from the ALMA-MaNGA QUEnching and STar formation (ALMaQUEST) survey, we investigate the parameters that correlate with variations in star formation rates on kpc scales. We use a combination of correlation statistics and an artificial neural network to quantify the parameters that drive both the absolute star formation rate surface density (ΣSFR ), as well as its scatter around the resolved star-forming main sequence (ΔΣSFR ). We find that ΣSFR is primarily regulated by molecular gas surface density (Σ _H_2 ) with a secondary dependence on stellar mass surface density (Σ⋆ ), as expected from an 'extended Kennicutt–Schmidt relation'. However, ΔΣSFR is driven primarily by changes in star formation efficiency (SFE), with variations in gas fraction playing a secondary role. Taken together, our results demonstrate that whilst the absolute rate of star formation is primarily set by the amount of molecular gas, the variation of star formation rate above and below the resolved star-forming main sequence (on kpc scales) is primarily due to changes in SFE.